2015
DOI: 10.1186/s12968-015-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial perfusion is impaired in asymptomatic renal and liver transplant recipients: a cardiovascular magnetic resonance study

Abstract: BackgroundMyocardial ischemia is a major cause of death in chronic kidney disease (CKD) patients, which can be caused by either epicardial or microvascular coronary artery disease (CAD). Although renal transplantation improves survival, cardiovascular disease remains a major cause of mortality in post renal transplant recipients, including those with no significant epicardial CAD pre-transplant. We aim to utilize stress cardiovascular magnetic resonance (CMR) and MR coronary angiography (MRCA) to assess silent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(41 reference statements)
0
4
1
Order By: Relevance
“…This finding supports the assumption that the duration of renal replacement therapy has a strong impact on myocardial perfusion, mainly due to rarefication of small intramyocardial vessels. 23 25 We found impaired CFR in 20% of our patients, which is less than reported in other studies 33 and most probably due to the relatively young study cohort. Prior investigations have suggested that CKD is associated with abnormal coronary vasodilator function, 26 which results from multiple mechanisms including decreased capillary density, 27 vascular remodeling, 28 and endothelial dysfunction.…”
Section: Discussioncontrasting
confidence: 71%
“…This finding supports the assumption that the duration of renal replacement therapy has a strong impact on myocardial perfusion, mainly due to rarefication of small intramyocardial vessels. 23 25 We found impaired CFR in 20% of our patients, which is less than reported in other studies 33 and most probably due to the relatively young study cohort. Prior investigations have suggested that CKD is associated with abnormal coronary vasodilator function, 26 which results from multiple mechanisms including decreased capillary density, 27 vascular remodeling, 28 and endothelial dysfunction.…”
Section: Discussioncontrasting
confidence: 71%
“…The spatial resolution of CMR myocardial perfusion (using most commonly adenosine) is superior to other imaging modalities, such as nuclear techniques, so that subendocardial ischemia can be more reliably identified [ 31 , 63 ]. Myocardial perfusion abnormalities can be attributed either to epicardial CAD or to microcirculation disorders, which are frequently present in LT candidates [ 64 ]. If CMR stress examination does not show ischemia in LT candidates, the 12-month event free survival rate is almost 100% [ 65 ].…”
Section: Cardiovascular Magnetic Resonance (Cmr)mentioning
confidence: 99%
“…Its high diagnostic accuracy in coronary heart disease and superiority over SPECT was established by the Clinical Evaluation of MAgnetic Resonance imaging in Coronary heart disease (CE-MARC) study [117]. Myocardial perfusion abnormalities can be attributed to epicardial CAD or microcirculation disorders and is frequently abnormal in cirrhotic patients [118]. A negative for ischemia CMR stress examination in LT candidates has been shown to have an almost 100% CAD event free survival at 12 months [119].…”
Section: Myocardial Ischemiamentioning
confidence: 99%